2011
DOI: 10.1186/1471-2458-11-11
|View full text |Cite
|
Sign up to set email alerts
|

The Cool Little Kids randomised controlled trial: Population-level early prevention for anxiety disorders

Abstract: BackgroundThe World Health Organization predicts that by 2030 internalising problems (e.g. depression and anxiety) will be second only to HIV/AIDS in international burden of disease. Internalising problems affect 1 in 7 school aged children, impacting on peer relations, school engagement, and later mental health, relationships and employment. The development of early childhood prevention for internalising problems is in its infancy. The current study follows two successful 'efficacy' trials of a parenting grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 46 publications
4
105
0
Order By: Relevance
“…Demographic factors suggest that social vulnerability, including low education, poor housing and no regular income, are risk factors for HIV infection in this population (5, 911), as it has been found in the South African population in general (49). Most behavioral variables are bivariately associated with HIV infection in the expected direction.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Demographic factors suggest that social vulnerability, including low education, poor housing and no regular income, are risk factors for HIV infection in this population (5, 911), as it has been found in the South African population in general (49). Most behavioral variables are bivariately associated with HIV infection in the expected direction.…”
Section: Discussionmentioning
confidence: 66%
“…Studies have shown that older MSM are more likely to be infected than younger MSM (8, 10, 11, 15, 17, 18, 21, 22), although incidence seems higher among younger MSM (7). HIV infection also seems to be associated with indicators of social vulnerability, including lower levels of education (9, 10), being unemployed (5), and low income (11). Behavioral risk factors for HIV infection in sub-Saharan MSM include having engaged in receptive anal intercourse (6, 8, 9, 11), number of sexual partners (15, 16), having been paid for sex (12, 16, 18, 21) (while having paid for sex seems to be a protective factor (9)), and having experienced violence (5, 17, 22).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of HIV positive MSM in South Africa who do not know their status has been found to be between 88% and 94% (15, 19). In a study that included Black and White South African MSM, ever having tested for HIV was associated with being Black, living in a township, and lacking social support (20).…”
Section: Introductionmentioning
confidence: 99%
“…A popular medium for improving parent wellbeing is social emotional parenting programs (e.g., 'Tuning into Kids'; Havighurst, Wilson, Harley, & Prior, 2009;and 'Cool Little Kids';Bayer et al, 2011). These programs are often delivered within a positive parenting framework, where an emphasis on parental warmth, acceptance, effective communication and behavioural management strategies aims to develop confident, caring and balanced parenting (The Positive Parenting Network of Australia, 2013; Sanders, 2008).…”
Section: Improving Parent Coping: Social Emotional Parenting Programsmentioning
confidence: 99%